ON THE LANZHOU INDEX OF GRAPHS - Tong, Qinghe; Yang, Chenxu; Li, Wen (International Journal of Research -GRANTHAALAYAH, 2022)
Let be a simple graph with vertex set and edge set . The Lanzhou index of a graph is defined by , where denoted by the degree of the vertex v in . In a chemical graph, the topological index can help determine chemical, biological, pharma-cological, toxicological, and technically relevant information on molecules. In this paper, we get exact formulas for , where is some certain chemical graphs, like silicate, chain silicate, oxide, and graphene networks. Moreover, we determine the Lanzhou index of several graph operations.